Feminisme Islam Dalam Novel Abidah El Khalieqy - Aning Ayu Kusumawati (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2013)
This article is a study of the text (read: fictional works Abidah El Khalieqy) is intended to express the idea of feminism, and also find a model or system of thought/Abidah El Khalieqy views on the relationship between Islam / religion with feminism. This study uses descriptive method. The purpose of the study using descriptive method is to create a description, picture, or drawing systematically and objectively, the facts, the properties, characteristics and relationships between existing elements or a particular phenomenon (in cultural studies ). This method is defined by Whitney - as quoted by M. Nazir - as a fact finding the correct interpretation. The fact in this context means that feminism and its impact among Muslims, and Abidah El Khaliqie view of the relationship between Islam (the religion) and Feminism in the works of fiction